Public sector reforms and public private partnerships: Overview and research agenda. Issue 1 (April 2017) - Caperchione, Eugenio; Demirag, Istemi; Grossi, Giuseppe
Abstract: The purpose of this editorial paper is to introduce the special issue and outline its majorthemes. This special issue of Accounting Forum aims to stimulate interdisciplinary and critical research on public sector reforms, particularly in the context of Public Private Partnerships and other public sector organisations. The editorial also seeks to provide a research agenda and new directions for more research in the field, considering the ambiguities of this hybrid organisational forms and the complexity of accounting and accountability reforms.